2015
DOI: 10.1111/jnc.13021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐181c negatively regulates the inflammatory response in oxygen‐glucose‐deprived microglia by targeting Toll‐like receptor 4

Abstract: Cerebral hypoxia/ischemia rapidly induces inflammation in the brain, which is characterized by microglial activation and the release of inflammatory cytokines. We have previously demonstrated that miR-181c can directly regulate tumor necrosis factor (TNF)-a production post-transcriptionally. Here, we determined that hypoxia up-regulated TLR4 expression but down-regulated miR-181c expression in primary microglia. We also demonstrated that miR-181c suppresses TLR4 by directly binding its 3 0 -untranslated region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 40 publications
5
73
0
Order By: Relevance
“…In addition, many other miR181c target genes regulate the cellular viability. It is reported that miR-181c protects neurons against injury under hypoxia by inhibition TLR4 expression, thus inhibiting NF-κB activation and the production of downstream proinflammatory mediators [54]. MiR-181c protects myocardial cells from apoptosis by targeting Bcl-2 protein, one of the anti-apoptotic members of the Bcl-2 family [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many other miR181c target genes regulate the cellular viability. It is reported that miR-181c protects neurons against injury under hypoxia by inhibition TLR4 expression, thus inhibiting NF-κB activation and the production of downstream proinflammatory mediators [54]. MiR-181c protects myocardial cells from apoptosis by targeting Bcl-2 protein, one of the anti-apoptotic members of the Bcl-2 family [55].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified an important role for the miR-181c-TLR4 pathway in hypoxic microglial activation and neuroinflammation. miR-181c was found to inhibit TLR4 expression by binding to its 3 0 -UTR, thus inhibiting NF-kB activation and the production of downstream proinflammatory mediators [20]. Hence, miR-181c is likely to be of importance in neuroimmunological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is determined that miR-181c negatively regulates TLR4 expression through its 3′-UTR. Furthermore, miR-181c suppresses NF-κB activation and its pro-inflammatory products including TNF-α, IL-1β, and iNOS [126]. In ischemic cerebral tissue, miR-155 induces the expression of TNF-α and IL-1β via upregulation of TLR4 and downregulates the expression of inflammatory mediators such as suppressor of cytokine signaling 1 (SOCS1) and the myeloid differentiation primary response gene 88 (MyD88) [127].…”
Section: Micrornas Intervention In Ischemic Stroke Progressionmentioning
confidence: 99%